2023
DOI: 10.1002/adfm.202302366
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy for Visualizing, Tracing, and Measuring the Gastrointestinal Absorption of Silver Nanoparticles

Abstract: The silver‐based formulation has become one of the most widely used nanoagents for agrifood industry and clinical translation. However, the in vivo fate of silver nanoparticles (AgNPs) via oral exposure remains poorly understood. Here, a specific strategy is shown for tracking the gastrointestinal transformation, intestinal absorption, and organ distribution of particulate Ag after oral exposure by using the gold (Au)‐Ag core−shell NPs (Au@AgNPs). Taking advantage of both plasmonic and elemental characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The sequentially digested AgNPs underwent significant alterations in particle size, zeta potential, and structure, but the dissolution of AgNPs at different phases in the GIT remains a mystery due to variations in pH, enzymes, and other components. , To unveil the possible mechanisms, the supernatants obtained at the end of each phase during digestion were gathered and subjected to analysis of the release of Ag + from AgNPs with ICP-MS. As shown in Figure A, compared with pAgNPs, both stAgNPs and estAgNPs had more Ag + release in three digestion phases, especially in SGF (pH 3) and SIF (pH 7). Previous studies showed that, in acidic solutions, oxidation dissolution may occur on the surface of AgNPs, resulting in the release of Ag + .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequentially digested AgNPs underwent significant alterations in particle size, zeta potential, and structure, but the dissolution of AgNPs at different phases in the GIT remains a mystery due to variations in pH, enzymes, and other components. , To unveil the possible mechanisms, the supernatants obtained at the end of each phase during digestion were gathered and subjected to analysis of the release of Ag + from AgNPs with ICP-MS. As shown in Figure A, compared with pAgNPs, both stAgNPs and estAgNPs had more Ag + release in three digestion phases, especially in SGF (pH 3) and SIF (pH 7). Previous studies showed that, in acidic solutions, oxidation dissolution may occur on the surface of AgNPs, resulting in the release of Ag + .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous animal studies have demonstrated that AgNPs could be found in the intestine after being orally ingested, and the chronic oral exposure to AgNPs damaged the epithelial cell microvilli and increased numbers of goblet cells in the intestine, suggesting that AgNPs may disorder the intestinal immune microenvironment. The accumulation of AgNPs in the intestine can causes inflammation, through damaging the epithelial barrier and activating immune cells. This leads to their infiltration in the intestinal lining, the activation of transcription factors like nuclear factor kappa B (NF-κB), and the release of inflammatory substances such as cytokines and chemokines. , Recent studies reported that the oral exposure of AgNPs can also induce disturbances in the gut microbiota. , Ultimately, these events will contribute to the development or worsening of various gut diseases, such as inflammatory bowel diseases (IBDs, such as Crohn’s disease and ulcerative colitis). Although the toxic effects of AgNPs in the gastrointestinal tract (GIT) have been confirmed, the gastrointestinal fate of AgNPs, including transformation and subsequent cellular interactions, remains not well understood, which is of key importance to assess their health risks. Consequently, an in vitro digestive simulation is necessary to specifically explore the correlation between the transformation and toxicity of AgNPs during gastrointestinal digestion.…”
Section: Introductionmentioning
confidence: 99%